Effect of Work Motivation on Sea Transportation Employee Performance - S. Syahyono (Program Studi Manajemen Institut Manajemen Koperasi Indonesia Bandung, 2021)
This research aims to deepen understanding of how work motivation can influence employee performance in the maritime transportation sector, with the hope that the results of this research can make a positive contribution to human resource development. The research method used is a survey method with correlational techniques. This means that the researcher did not carry out treatment on the variables studied. Meanwhile, the data collection tool used was a questionnaire in the form of a questionnaire. In this study, it was concluded that leadership, education, employee age, length of service, gender, distance from home to office, employee origin, work environment, work atmosphere, employee morale and character, employee character, existing work facilities and other factors others, which means that 79.20% of employee performance is influenced by this, while the remaining 20.80% is influenced by the employee's own motivation